Evaluation of Authentic Assessment Implementation on Biology Learning at Senior High Schools in Semarang - Kusumawati, Vita; Susilowati, Sri Mulyani Endang; Isnaeni, Wiwi (Journal of Innovative Science Education, 2021)
Authentic assessment is an assessing technique on 2013 curriculum learning. Authentic assessment assesses learning process and students’ learning outcomes. This research aims to evaluate authentic assessment implementation on Biology learning at 4 Public Senior High Schools (SHS) in Semarang. This descriptive qualitative research used CIPP (context, input, process, and product) evaluative model. The data was taken by observing, interviewing, and analyzing instrument quality used by the teacher during learning. The data was analyzed by using Milles & Huberman model which consisted of reduction, display, and conclusion. The findings of authentic assessment implementation showed various outcomes. The authentic assessment instrument development of Public SHS A, B, C, and D’s biology teachers in Semarang was generally categorized excellent or high. All teachers had obtained 2013 curriculum learning training through Biology teacher discussion. The teachers were regularly supervised once in a year. The process of biology authentic assessment implementations at SHS A, B, C, and D in Semarang were categorized sufficient or moderate. The findings showed that SHS A student learning outcome average was 51; SHS B was 72; SHS C was 63; and SHS D was 73. The hindrances of the SHS A, B, C, and D’s teachers in implementing the assessment dealt with cognitive, affective, and psychomotor aspects of the students simultaneously during each learning.